Three Alternatives for Graphing Behavioral Data: A Comparison of Usability and Acceptability. Issue 1 (January 2022) - Kinney, Chad E. L.; Begeny, John C.; Stage, Scott A.; Patterson, Sierra; Johnson, Amirra
Making treatment decisions based upon graphed data is important in helping professions. A small amount of research has compared usability between equal-interval and semi-log graphs, but no prior studies have compared different types of semi-log graphs. Using a randomized, cross-over, experimental design with 72 participants, this study examined the relative usability and acceptability of three types of graphs: Regular (equal-interval), Standard Celeration Chart (SCC; semi-log), and Standard Behavior Graph (SBG; semi-log). All participants used each graph across three usability tasks (Plotting Data, Writing Values, and Interpreting Trends). For the Plotting and Writing tasks, the equal-interval graph produced the greatest rate of correct responses. However, for the Interpreting task the SBG produced the greatest rate of corrects, while the equal-interval graph produced the smallest rate. User acceptability mainly favored the equal-interval and SBG graphs. Study findings and implications are discussed with respect to graph usability and acceptability during day-to-day practice.